World Religions the great faiths explared & explained - Bowker, John 1935- (Dorling Kindersley Limited, 2003)
Baffled by Buddhism? Confused by Catholicism? Explore the faith and practices of the world's religions in this richly illustrated and accessible volume. Every denomination is examined in detail through sacred texts, epic imagery, key beliefs and religious artefacts